Lung ultrasound in the diagnosis and monitoring of 30 children with coronavirus disease 2019. Issue 5 (12th January 2021) - Musolino, Anna Maria; Supino, Maria Chiara; Buonsenso, Danilo; Papa, Raffaele Edo; Chiurchiù, Sara; Magistrelli, Andrea; Barbieri, Maria Antonietta; Raponi, Massimiliano; D'Argenio, Patrizia; Villani, Alberto; Tomà, Paolo; ,
Abstract: Background: The coronavirus disease 2019 (COVID‐19) has caused a new global pandemic and is responsible for millions of infections and thousands of deaths in the world. The lung ultrasound (LUS) is a noninvasive and easily repeatable tool and can be carried out by the pediatrician at the bedside of children with a consequent reduction in the risk of transmission of the virus. Objective: We hypothesized that ultrasound findings in these patients would (1) be associated with their disease severity and (2) change over time in alignment with clinical outcome. Methods: The study was made in the emergency department (ED) in a tertiary level pediatric hospital. All patients with swab‐confirmed COVID‐19 infection were subjected to a LUS within 6 h from admission and after 96 h. Results: Among a total of 30 children, 18 (60%) were males, 4 reported exertional dyspnea, and only 1 chest pain. The mean oxygen saturation was 98.8 ± 1.0% in ambient air in the ED and no patient needed oxygen therapy during hospitalization. Children with moderate disease presented more B line ( p = .03). After 96 h, we had observed ultrasound abnormality only in 20% of the children. We found a statistically significant reduction in pleural irregularities (30% vs. 16.7; p = .001) and in B lines (50% vs. 20%; p = .008). Conclusions: The LUS is a useful, feasible, and safe tool for the clinician to complement the clinical evaluation and to monitor the evolution of lung disease in children with COVID‐19.